Angiotensin II, tissue factor and the thrombotic paradox of hypertension. (December 2010) - Celi, Alessandro; Cianchetti, Silvana; Dell'Omo, Giulia; Pedrinelli, Roberto
Tissue factor (TF), the physiologic initiator of blood coagulation, may contribute to the increased risk of thrombotic complications that characterizes arterial hypertension, as suggested by hypertensive animal models showing evidence for TF activation, and clinical studies in hypertensive patients at higher cardiovascular risk with increased circulating levels of TF and thrombogenic microparticles. Angiotensin II stimulates TF expression both in vitro and in vivo, an effect abolished by ACE or angiotensin II receptor inhibition. Moreover, renin–angiotensin system blockers, including aliskiren, a direct renin inhibitor, are able to modulate TF expression in monocytes and vascular endothelial cells activated by inflammatory cytokines. This behavior is suggestive of anti-inflammatory and anti-thrombotic properties of renin–angiotensin system blockers, and is compatible with the possibility that blocking local renin–angiotensin system activation might downregulate TF, thus reducing the risk of ischemic complications in hypertensive patients.